ANALISIS KESULITAN BELAJAR MAHASISWA DALAM KULIAH ONLINE (Studi pada Mahasiswa Bimbingan Konseling Islam UIN Imam Bonjol Padang) - Afnibar Afnibar; Dyla Fajhriani. N; Ahmad Putra (Universitas Islam Negeri Imam Bonjol Padang, 2020)
ABSTRACTLearning difficulties is a condition in which a person cannot learn properly, because there are certain disorders. In the learning process students are often found to have difficulty in learning, which affects the learning outcomes achieved. Learning difficulties are caused by various factors, both internal and external factors. The purpose of this study is to find out in detail and comprehensively the difficulties of student learning in online lectures. The research method used is qualitative research. The data source is 60 students majoring in Islamic Counseling Guidance. Data collection is done through online media utilizing 2 (two) WhatsApp groups. The results obtained were that most students said that they did not understand what the lecturer explained, the limited learning resources (such as books that were not available), it was difficult to discuss with friends because many friends did not understand either, there was no practice for lectures that should have been practical, limited time given by lecturers to complete assignments, many disturbances both from the learning environment that is not conducive or other tasks given by parents. A small number of students said that they did not have an android mobile phone, so they borrowed a parents or olders handphone, and it was difficult to get internet access.